ANALISIS KEBIJAKAN DIVIDEN PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS IDX30 - RIo Montella, (2021)
This study is a quantitative study designed to determine the impact of profitability, leverage, and inflation on dividend policy. This study uses samples from companies indexed by IDX30. During the determination of the sample, the researcher used the purposive sampling method. For hypothesis tests to use the analysis of the data panel regression with the E-Views program. The conclusion of this study is that profitability has a significant positive effect on dividend policy, leverage has no effect on dividend policy, and inflation has no effect on dividend policy. In addition, these three variables have a simultaneous influence on dividend policy.